Ekoteologi Islam dan Kearifan Agraris Kejawen: Relasi Tuhan, Manusia, dan Alam di Wonosobo - Ahmad Taqwin; Maharsi; Moh. Soehada (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
Previous studies on Islamic ecotheology have predominantly emphasized the normative-doctrinal dimensions of environmental ethics, while the implementation of ecological theology in the lived practices of local Muslim communities, particularly through agrarian rituals and traditional ecological knowledge, remains underexplored. This study addresses that gap by analyzing the relationship between God, humans, and nature in the traditional agricultural practices of the Javanese Islamic (Kejawen) community in Lengkong Village, Wonosobo Regency. Employing a qualitative ethnographic design, data were collected through participant observation, in-depth interviews, and documentation with farmers and community elders, and were analyzed thematically using NVivo software. The findings reveal that agricultural practices in Lengkong constitute a lived ecotheology in which the Qur’anic concepts of khalifah (vicegerency), amanah (trust), mizan (cosmic balance), and ayat kauniyah (cosmic signs) are articulated not through doctrinal texts but through embodied ritual practice, planting prayers, symbolic offerings (sesaji), incense burning, and cosmologically oriented land management. The study also finds that the traditional Pranata Mangsa agrarian calendar is no longer directly employed due to climate-induced seasonal disruption and agricultural modernization; yet its underlying ecological ethic persists through adaptive negotiation between traditional knowledge and farmers’ empirical experience. This study contributes to contemporary Islamic ecotheological discourse by demonstrating how local agrarian traditions function as a form of environmental ethics rooted in Islamic spirituality and Javanese cosmology, thereby repositioning ecotheology from a normative doctrine toward a practiced, embodied ethic relevant to global debates on indigenous ecological knowledge and climate adaptation.